Rapid decline in estimated glomerular filtration rate in sickle cell anemia: results of a multicenter pooled analysis - Ataga, Kenneth I.; Zhou, Qingning; Derebail, Vimal K.; Saraf, Santosh L.; Hankins, Jane S.; Loehr, Laura R.; Garrett, Melanie E.; Ashley-Koch, Allison E.; Cai, Jianwen; Telen, Marilyn J. (Haematologica (Roma), 2021)
Not available.Not available.